2021
DOI: 10.3390/ijms222112040
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SELENOF Induces the Transformed Phenotype in Human Immortalized Prostate Epithelial Cells

Abstract: SELENOF is a member of the class of selenoproteins in which the amino acid selenocysteine is co-translationally inserted into the elongating peptide in response to an in-frame UGA codon located in the 3′-untranslated (3′-UTR) region of the SELENOF mRNA. Polymorphisms in the 3′-UTR are associated with an increased risk of dying from prostate cancer and these variations are functional and 10 times more frequent in the genomes of African American men. SELENOF is dramatically reduced in prostate cancer compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Recent data indicate that the depletion of SELENOF in cultured human cells or in Selenof KO animal models leads to differential expression of metabolism-related genes and associated phenotypes. Using immortalized human prostate epithelial cells, knockdown of SELENOF with an siRNA construct resulted in increased mitochondrial respiration and presumably ATP synthesis, increased phosphorylation and activation of AMP-activated protein kinase and inhibition by phosphorylation of acetyl CoA carboxylase, key proteins in regulating energy metabolism [ 50 ]. SELENOF was reported to bind to retinol dehydrogenase 11 and its overexpression led to reduced retinol production indicating that SELENOF may also play a role in vitamin A metabolism [ 51 ].…”
Section: Selenof’s Putative Roles In Redox Protein Quality Control An...mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent data indicate that the depletion of SELENOF in cultured human cells or in Selenof KO animal models leads to differential expression of metabolism-related genes and associated phenotypes. Using immortalized human prostate epithelial cells, knockdown of SELENOF with an siRNA construct resulted in increased mitochondrial respiration and presumably ATP synthesis, increased phosphorylation and activation of AMP-activated protein kinase and inhibition by phosphorylation of acetyl CoA carboxylase, key proteins in regulating energy metabolism [ 50 ]. SELENOF was reported to bind to retinol dehydrogenase 11 and its overexpression led to reduced retinol production indicating that SELENOF may also play a role in vitamin A metabolism [ 51 ].…”
Section: Selenof’s Putative Roles In Redox Protein Quality Control An...mentioning
confidence: 99%
“…Additional interest in SELENOF in relation to prostate cancer was sparked by the observation that polymorphisms in SELENOF gene were associated with prostate cancer mortality among participants of the Physician’s Health Study [ 58 ]. Examination of human prostate tissue from two different tissue microarrays indicated that SELENOF co-localized with the plasma membrane in benign prostate tissue and immortalized human prostate cells in contrast to its location in other tissues where it resides in the EnR [ 38 , 50 ]. Moreover, SELENOF levels were significantly lower in prostate cancer samples compared to adjacent benign tissue, raising the possibility that the loss of SELENOF in prostate cancer was contributing to oncogenic progression.…”
Section: Selenof Activities In Different Types Of Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, selenium deficiency is discussed in the setting of cardiovascular function [ 6 ] and as a trigger for autoimmune diseases [ 7 ]. This Special Issue also provides insights into selenoprotein mechanisms, including SELENOF in prostate [ 8 ] and colon cancers [ 9 ], SELENOI in immune response [ 10 ], SELENOW’s interaction with thioredoxins [ 11 ], and SELENOP-mediated selenium transport in Hashimoto`s thyroiditis [ 12 ]. Furthermore, an overview of the pathogenic variants in selenoproteins genes from a population genomics perspective [ 13 ], a review on the human genetic disorders resulting in systemic selenoprotein deficiency [ 14 ], and a new strategy to assess the selenoproteome by non-radioactive isotopic labeling are presented [ 15 ].…”
mentioning
confidence: 99%